UNESCO World Heritage Convention – mission and commitment in times of challenges: lessons learnt from World Heritage Cities in Northwest-Europe and North-America - Matthias Ripp; Elena Arndt; Monika Göttler (Ochrona Dziedzictwa Kulturowego)
This article is based on a presentation given at the International Conference “50 years UNESCO World Heritage Convention in Europe: Achievements and Challenges” in Krakow/Poland in June 2022. The purpose is to showcase current challenges for UNESCO World Heritage Cities, how they are connected and how cities can respond to the challenges by installing heritage site managers. The described challenges are based on reports and work within the Organisation of World Heritage Cities (OWHC), the analysis and elaboration of the roles and skills of site managers of previous published work.